The effects of the exercises of segmental stabilization in low back pain - Barradas, Layanna Patrícia Freitas; Silva, Luiz Fernando Batista Pereira da; Sousa, Rayssilane Cardoso de; Matos, Ludmilla Karen Brandão Lima de; Carvalho, Ana Flávia Machado de (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Low back pain is responsible for a large part of painful disorders in clinical practice, causing limitations in physical activities and professionals. Physical Therapy has directed its techniques in the prevention and relief of symptoms of this disease of the spine, making use of exercises, like the segmental stabilization. Objective: To verify the effects of exercises of segmental stabilization in low back pain. Method: It was an experimental study of longitudinal quantitative approach with sample of 10 participants with complaint of low back pain. The participants were randomly divided into control and experimental group and after they were assessed through of sheets containing data of identification and the variables (pain, flexibility and balance). The experimental group was treated during six weeks with segmental stabilization and, at the end of the last session, all participants were reassessed. The data were organized in Microsoft Office Excel program, submitted to Student’s T test with significance at p<0.05 for analysis in the statistical program Graph Pad Prism 5.0. Results: There was significant improvement in low back pain of the participants after the interventions, but in relation to other variables of the study were obtained only a numerical gain in absolute terms, although not significantly. Conclusion: The segmental stabilization provided significant effects on low back pain, indicating that this technique can be used by Physiotherapist in their conducts, however, it is suggested new researches with larger sample in order to obtain better in relation to other variables